The sonnets - Shakespeare, William (Blaisdell, 1968)
John Dover Wilson's New Shakespeare, published between 1921 and 1966, became the classic Cambridge edition of Shakespeare's plays and poems until the 1980s. The series, long since out-of-print, is now reissued. Each work contains a lengthy and lively introduction, main text, and substantial notes and glossary.